STRATEGI PENGEMBANGAN AGROWISATA DI PERKEBUNAN KOPI GAYO DESA GUNUNG SUKU KABUPATEN ACEH TENGAH - Ihyana Hulfa; Ander Sriwi; Rizal Kurniansah (Sekolah Tinggi Pariwisata Mataram, 2021)
Gunung Suku Village has a natural, social cultural appeal that is very diverse and potentially become a tourist attraction, but this potential tourism has not been developed well and maximal to becomes a tourist destination. This study aims to formulate effective strategies for the development of agrotourism in Gunung Suku Village. This study uses qualitative methods, data collection through observation, in-depth interviews, questionnaires and literature study. Purposive sampling used in this study for determination of sample, Data analysis in this study used qualitative descriptive approach, IFAS, EFAS and SWOT analysis. The results of this study indicate the potential of coffee plantation areas has not been developed, due to the lack of human resources, accessibility, facilities and infrastructure of tourism activities and the weak role of local government. The general strategy is in quadrant II, namely the development strategy of attractiveness. Alternative strategies (1) SO strategies (a) Strategies for developing potential to the fullest, (b) Strategies for developing marketing and promoting tourist attraction, (c) Development strategies for making tour packages. (2) ST Strategy (a) Community-based agrotourism development strategy, (b) Development Strategy by highlighting different potentials from other regions. (3) WO Strategy (a) HR development strategies especially in the field of tourism, (b) Accessibility development strategies, (c) Strategies to develop places to stay, eat drinks and gift shops. (4) WT Strategy (a) Increasing Public Awareness to conserve and preserve local culture, as well as the emergence of many competitors, (b) Increase cooperation with all stakeholders, (c) Improve the development of human recources in the tourms sector. Agrotourism development requires cooperation with all stakeholders in order to improve the qualityof human resources, accessibility, facilities and institutions, so that it has a direct impact on the income of the villagers of Gunung Suku Village.